PENDUGAAN POTENSI AIR TANAH DENGAN METODA RESISTIVITAS DUA DIMENSI DI WILAYAH PESISIR UNTUK PERENCANAAN PEMBANGUNAN AIR BERSIH DI KABUPATEN PASIR, KALIMANTAN TIMUR - Indriatmoko, Robertus Haryoto; Herlambang, Arie (Jurnal Air Indonesia, 2005)
Pasir Regency (Tanah Grogot) has coastal areas which is potential economically. To support the development of the area the local government is planning the development of proper and efficient plan to overcome the water problem of a coastal area. The plan could be implemented by conducting geophysical research and analysis of water quality of existing water resources. Based on this research hopefully an economically proper and efficient plan to develop the potency of existing water resources will be implemented. Katakunci : Wilayah Pesisir, Dua Dimensi, Geofisik, Akuifer, Air Tanah, Kualitas Air, Kabupaten Pasir,Tanah Grogot